Early-life development of spleen in white rabbit (Oryctolagus cuniculus): A morphometric and histochemical analysis: https://doi.org/10.12982/VIS.2025.012 - Altaey, Omar Younis; Hasan, Ali Ahmed; Alhaaik, Ammar Ghanim (Veterinary Integrative Sciences, 2024)
The spleen's significant immunological and protective role has long inspired researchers to explore its developmental characteristics. This study intended to understand the splenic morphological developmental changes during postnatal life. Samples obtained form 25 (Oryctolagus cuniculus) white rabbits, divided into five age groups in :1, 10, 15, 30, and 90 postnatal days. The samples were measured to determine the length, breadth, thickness, and weight. afterward, the samples sectioned and stained using hematoxylin and eosin (H&E) and Masson's trichrome stains (MTs). And for histochemical analysis, additional slides were stained with Periodic acid schiff (PAS) and Alcian blue (AB) 2.5 pH stains. The histological measurements included the thickness of the capsule and trabeculae, diameter of white pulp follicle, and central artery, and the ratio of white and red pulps. The macroscopic findings showed a significant increase in dimensional measurements. Histologically, the capsule and trabeculae exhibited thickening, and the diameter of the white pulp follicles and central arteries expanded. And the splenic sinuses enlarged with age progression. The histochemical evaluation revealed intense staining with PAS in the capsule, trabeculae, and walls of splenic arteries in first postnatal day group, with moderate staining affinity in the other groups. Furthermore, there was positive staining with AB in the white pulp follicles of the first postnatal day group compared to weaker staining affinity in the older age groups. This study demonstrated that the critical development period begins after birth and continues until 30 postnatal days. During this period, the development of the immune response triggers significant alterations in the spleen's structural, morphometric, and histochemical parameters.